The Turning Point of the Aerosol Era. (27th December 2022) - Bauer, Susanne E.; Tsigaridis, Kostas; Faluvegi, Greg; Nazarenko, Larissa; Miller, Ron L.; Kelley, Maxwell; Schmidt, Gavin
Abstract: Over the CMIP6 historical period (1850–2014), aerosols provided the largest negative forcing compared to all other climate forcings via their ability to absorb or scatter solar radiation and alter clouds. Aerosols played an important role in counterbalancing warming by greenhouse gases (GHGs). Here we study aerosol forcing trends in the CMIP6 simulations of the NASA Goddard Institute for Space Studies (GISS) ocean‐atmosphere ModelE version 2.1 (GISS‐E2.1‐G) using a fully coupled atmospheric composition configuration, including interactive gas‐phase chemistry, and either an aerosol microphysical (MATRIX) or a mass‐based aerosol (OMA) module. Simulations of the CMIP6 historical period are analyzed as well as four Shared Socioeconomic Pathway (SSP) future scenarios for 2015–2100: SSP1‐2.6, SSP2‐4.5, SSP3‐7.0, and SSP5‐8.5. The main conclusion of this study is that aerosol forcing in the GISS model has reached its turning point, switching from globally increasing to a decreasing trend in the first decade of the 21st century. This result is robust, independent of which aerosol module or SSP scenario is used. Non‐linear aerosol‐cloud interactions dominate as a forcing agent over aerosol‐radiation interactions. Aerosols' ability to counterbalance GHG forcing on the global scale is today at a level comparable to that at the beginning of the last century. In the 1980s, the decade of largest global aerosol loads, aerosols balanced up to 80% of GHG forcing. As a consequence, global warming of the last decades, which is primarily driven by greenhouse gases, has been augmented by the effect of decreasing aerosol cooling in our model. By the end of this century, following the SSP scenarios, aerosols will only counterbalance 0%–20% of GHG forcing, depending on model and on scenario. Plain Language Summary: Climate change is the result of the aggregate effect of a number of individual forcing agents changing the radiative balance at the top of the atmosphere over time. As a result, if positive radiative forcings dominate over negative forcings, the Earth's surface warms. Over the historical period, since the pre‐industrial era, greenhouse gases (GHG) and aerosol have provided the largest positive and negative forcings, respectively. However, the relationship between GHG and aerosols have rapidly changed in the last decades, and future projections show much more dramatic dominance of GHG over aerosols. This study investigates the connection between emissions, atmospheric composition and climate forcing. We find that aerosols' ability to counterbalance GHG forcing reached its maximum effect in the 1980s, and that since the first decade of the 21st century, aerosol effects are globally on a decreasing trajectory. Reduced aerosol loads are important for health, but accelerate global warming, in the absence of concurrent GHG reductions. The results presented here are based upon the NASA GISS climate model, and the four future scenarios used. These scenarios are not intended as predictions, but represent a range of possible changes in atmospheric composition (including greenhouse gases) based on differing assumptions about future energy policies. Key Points: Aerosol forcing in the Goddard Institute for Space Studies model reached its turning point in the first decade of the 21st century Non‐linear aerosol‐cloud forcing dominates in magnitude over aerosol direct forcing and pinpoint the timing of the turning point Within the next 25 years, global aerosol forcing might balance only 0%–20% of greenhouse gas forcing, compared to 80% in 1980–1990